Comparative Study between Three-Dimensional Transvaginal Ultrasonography and Hysteroscopy in Patients with Abnormal Uterine Bleeding at Birat Medical College Teaching Hospital - Khadka, Roshana; Yadav, Ajay; Man Singh Karki, Gyanendra; Dahal, Prerana; Taparia, Sushil (Birat Journal of Health Sciences, 2024)
Introduction: Hysteroscopy has been a gold standard in diagnosis of various uterine pathologies which are potential uterine causes of abnormal uterine bleeding (AUB) Recently Transvaginal 3D ultrasonography (3D USG) has boomed as a non-invasive imaging technique which promises to be resourceful in the detection and evaluation of pelvic pathologies contributing to the causes of AUB. Objective:To compare the diagnostic accuracy of 3D USG and Hysteroscopy in evaluation of the causes of abnormal uterine bleeding Methodology : A cross sectional study conducted in the department of Radiodiagnosis and the department of Obstetrics and Gynecology (OBG) at Birat Medical College and Teaching Hospital enrolling 70 participants with history of abnormal uterine bleeding who consented for undergoing TVS and Hysteroscopy. Results: 3D TVS and Hysteroscopy , both revealed notable differences in their diagnostic abilities. 3D TVS identified myomas in 56.25%, particularly detecting intramural myomas in 37.5%, which Hysteroscopy failed to identify. In contrast, Hysteroscopy was more effective at detecting submucosal myomas (42.86%) and polyps (42.86%), outperforming 3D TVS in both categories. Detection rates for hyperplasia were comparable, and both methods detected endometrial mass in one case each. These findings suggest that the two techniques complement each other in the evaluation of uterine abnormalities. Conclusion : While 3D TVS is more effective at detecting intramural myomas, Hysteroscopy has a higher detection rate for submucosal myomas and polyps,exhibiting the complementary roles of these diagnostic techniques. KEYWORDS Abnormal Uterine Bleeding (AUB), Hysteroscopy, 3D Ultrasonography (3D USG), Transvaginal ultrasonography (TVS)